1996
DOI: 10.1364/ao.35.007091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the optical extraction efficiency in gas-flow lasers with different types of resonator

Abstract: The celebrated Rigrod model [J. Appl. Phys. 34, 2602 (1963)] has recently been shown to be inadequate for calculating the output power of gas-flow lasers when the quenching of excited species is slow and the optical extraction efficiency is high [Opt. Lett. 20, 1480 (1995)]. The previous analysis of two-level systems is presented here in detail and extended to include the chemical oxygen-iodine laser (COIL). For both two-level systems and COIL's, we obtained simple analytic formulas for the output power, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In the SGK model, the gas kinetic equations that describe the translational velocity distributions of particles in the upper and lower iodine energy levels are presented and a method for solving these equations is developed. In the deduction of this model, a gain coefficient related to the translational velocity of lasing particles is introduced gT= aØ(v,v0)(f2 -ca';), (3) where O is the pressure dependent stimulated emission cross section, f, (i 1,2) is the velocity distribution of upper and lower laser level, respectively. V0 ) is the Lorentz profile function, a is a constant related to level degeneracy, for the COIL a 1/ 2 , v and V0 are the laser radiation frequency and the central frequency of the spectral line profile, respectively.…”
Section: Gain Saturation Equation Of the Sgk Model In Flowing Coilmentioning
confidence: 99%
“…In the SGK model, the gas kinetic equations that describe the translational velocity distributions of particles in the upper and lower iodine energy levels are presented and a method for solving these equations is developed. In the deduction of this model, a gain coefficient related to the translational velocity of lasing particles is introduced gT= aØ(v,v0)(f2 -ca';), (3) where O is the pressure dependent stimulated emission cross section, f, (i 1,2) is the velocity distribution of upper and lower laser level, respectively. V0 ) is the Lorentz profile function, a is a constant related to level degeneracy, for the COIL a 1/ 2 , v and V0 are the laser radiation frequency and the central frequency of the spectral line profile, respectively.…”
Section: Gain Saturation Equation Of the Sgk Model In Flowing Coilmentioning
confidence: 99%
“…[1][2][3] From the deduction and analyses above, it can be concluded that RE model can consider conditions of inhomogeneous broadening being predominant and both homogeneous and inhomogeneous broadening being of importance, and it can predict effects of pressure and frequency shift on the performance of COIL. However the RE model cannot consider frequency characteristics of the spectral line profile and cannot explain the anomalous gain saturation in HF͞DF chemical laser experiments.…”
Section: Comparison With Sgk Modelmentioning
confidence: 99%
“…The most widely used theoretical model is still the rate-equation ͑RE͒ model, or its low-pressure limit in COIL. [1][2][3] In this paper, a modified RE model that is adapted to both the condition of homogeneous broadening and inhomogeneous broadening being of importance and the condition of inhomogeneous broadening being predominant is presented.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15]. The basis of this approach is so-called the two-level generation model where the population kinetics of levels is determined solely by energy-exchange process (1) and by process of stimulated emission at the frequency in the center of a spectral line of transition ( ) ( )…”
Section: Introductionmentioning
confidence: 99%
“…This approach provides simple dependences of OIL energy characteristics on several dimensionless similarity criteria 13 . The two-level generation model predicts the extraction efficiency of OIL with good accuracy [11][12][13][14][15] when energy losses in the relaxation processes are negligible.…”
Section: Introductionmentioning
confidence: 99%